Quality index efficiency analysis for sorting and composting plants (Research, Society and Development, 2022)
The general objective of the article is to analyze the efficiency of a quality index directed to sorting and composting plants in order to evaluate the operational, organizational and environmental quality of sorting and composting plants through the Driving Force - Pressure - Impact - State model. – Response (FPIER), as well as assessing whether the aforementioned index has established cause and effect links that underlie the FPIER model, in order to qualify the projects as in inadequate, acceptable or adequate conditions. The index analyzed was structured in the form of a questionnaire involving nine indicators: location, legalization, amount of solid waste, working conditions, infrastructure, sorting and composting process, socio-environmental responsibility, administrative processes and analytical processes. For this, the methodology used in the study was based on a qualitative research through a bibliographic survey and also a case study in order to analyze the efficiency of that index. The index analyzed made it possible to evaluate and classify the operational, organizational and environmental quality of the sorting and composting plant in the municipality of São José do Rio Preto properly and efficiently, in addition to clearly establishing links between causes and effects, a very positive factor for the mobilization of involved in order to improve the conditions of the enterprise.